Factors Affecting Belief In Fake News Related To Covid-19 In China: A Dual Information Processing Perspective - Wu, Yanhong (2024)
During covid-19, social media in china was overwhelmed with fake news. People often believe in fake news on social media, which can be harmful to individuals, society, and the country. However, little research has been conducted on the belief in fake news in the chinese context. This study aims to determine the influence of message, individual, and situational factors on belief in fake news on social media in china during covid-19 from a dual-process information processing perspective, as well as the impact of status-seeking on the relationship between information processing and belief in fake news. In order to empirically test and validate an integrated research model and achieve the research objectives, this study employed survey method and applied various statistical techniques. An online questionnaire was distributed in eight residential neighbourhoods in beijing, china, and a total of 813 valid responses were collected from social media users aged 18–65. Ibm spss and smartpls were used to examine the data, empirically test the research model, and answer the research questions posed in this study. Results indicated that message factors (perceived message attractiveness and quality), individual factors (risk propensity and narcissism), and situational factors (information overload and perceived uncertainty) positively influenced information processing (heuristic and systematic processing) and belief in fake news. Status-seeking motivation positively moderated the relationship between systematic processing and belief in fake news.